Cyber Ireland - Lynch, C. author. aut Link
IX, 178 p.
Keywords: Cyber Ireland explores, for the first time, the presence and significance of cyberculture in Irish literature. Bringing together such varied themes as Celtic mythology in video games, Joycean hypertexts and virtual reality Irish tourism, the book introduces a new strand of Irish studies for the twenty-first century.